2014
DOI: 10.1007/s00403-014-1454-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations in sporadic basal cell carcinomas

Abstract: Basal cell carcinoma (BCC) is the most common malignant human neoplasm characterized by slow growth and virtual absence of metastases. Recently, it has become evident that along with genetic mutations epigenetic alterations play a key role in the pathogenesis of human cancer. We searched for promoter methylation of hMLH1, RASSF1A, DAPK, APC, DCR1 and DCR2 genes and BRAF mutations in BCCs in association with the clinicopathological parameters and the histological subtypes of the tumours. Fifty-two BCCs, 17 FFPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…therapy (Berdasco and Esteller, 2019). Cancer-related genes found silenced in basal cell carcinoma are CDH13, SFN, TNFRSF10C, FHIT, SHH, APC, SFRP5, and RASSF1 (Brinkhuizen et al, 2012;Goldberg et al, 2006;Lodygin et al, 2003;Stamatelli et al, 2014;Takeuchi et al, 2002). Genes inactivated in cSCC are, for instance, the tumor suppressors CDKN2A, RB1, and CDH1 (Brown et al, 2004;Murao et al, 2006), and silencing of MIR204 appears to be involved in the progression from AK to cSCC (Toll et al, 2016).…”
Section: Dna Methylation Deregulation In Epidermal Cancersmentioning
confidence: 99%
“…therapy (Berdasco and Esteller, 2019). Cancer-related genes found silenced in basal cell carcinoma are CDH13, SFN, TNFRSF10C, FHIT, SHH, APC, SFRP5, and RASSF1 (Brinkhuizen et al, 2012;Goldberg et al, 2006;Lodygin et al, 2003;Stamatelli et al, 2014;Takeuchi et al, 2002). Genes inactivated in cSCC are, for instance, the tumor suppressors CDKN2A, RB1, and CDH1 (Brown et al, 2004;Murao et al, 2006), and silencing of MIR204 appears to be involved in the progression from AK to cSCC (Toll et al, 2016).…”
Section: Dna Methylation Deregulation In Epidermal Cancersmentioning
confidence: 99%
“…Importantly, they found Shh, adenomatous polyposis coli (APC), secreted frizzled‐related protein 5 (SFRP5), and Ras association domain family 1A (RASSFIA) to be more methylated in BCC versus normal skin . Another study found similar results in which they analyzed 52 sporadic BCCs and found five genes to show variable frequency of methylation (14–44%), those include DCR2, DCR1, RASSFIA, APC, and death associated‐protein kinase (DAPK) promoter . However, another group irradiated human keratinocytes several times with UVB radiation and analyzed the DNA methylation of the irradiated cells versus non‐irradiated cells; and found no difference of DNA methylation between the two groups .…”
Section: Genetic and Epigenetic Factors In Bcc Developmentmentioning
confidence: 87%
“…Many pathways play a role in promotion of mesenchymal protein expression including RAS/RAF/ MEK/ERK, PI3K/AKT/mTOR, Wnt/b-catenin, and several others. 34 Hypermethylation of specific tumor suppressor genes, as well as those involved in cell-cycle regulation, DNA repair, cell signaling, transcription, and apoptosis, have been reproducibly described in cutaneous melanoma. The CDKN2A promoter has been shown to be hypermethylated in a substantial fraction of primary cutaneous melanoma samples and is associated with both increased Ki-67 index and reduced patient survival.…”
Section: Malignant Melanomamentioning
confidence: 99%
“…The expression of aVb3 integrin, which, in addition to E-cadherin loss and N-cadherin expression, also tightly associates with the transition from the radial-to vertical-growth phase in melanoma. 34…”
Section: Malignant Melanomamentioning
confidence: 99%